Let’s Read Application Improves Junior High School Students’ Reading Skills - Hariyanti, Widya; Fitrilia, Ise; Kalsum , Umi (Indonesian Journal of Innovation Studies, 2025)
Background (General): Reading comprehension is a fundamental skill in language learning, essential for academic success and lifelong learning. Background (Specific): In the Indonesian junior high school context, students often struggle with reading comprehension due to limited access to engaging and interactive learning tools. Knowledge Gap: Despite the increasing availability of digital media, empirical evidence on the effectiveness of mobile reading applications like Let’s Read in improving students' reading comprehension remains limited. Aims: This study aimed to examine the effectiveness of the Let’s Read application as a digital learning tool to enhance reading comprehension among eighth-grade students at SMP Muhammadiyah Pagar Alam. Results: Using a quasi-experimental design with pre-test and post-test assessments, findings revealed that students in the experimental group—who used Let’s Read—demonstrated significantly higher gains in identifying main ideas, understanding contextual vocabulary, and making inferences compared to those taught with conventional methods. Novelty: The study provides new evidence on how interactive digital applications can enhance specific reading sub-skills in a formal educational setting. Implications: These results underscore the potential of integrating digital reading platforms into English language instruction to foster more effective and engaging learning experiences for junior high school students. Highlights : Demonstrates the effectiveness of Let’s Read in enhancing reading sub-skills. Fills the gap in research on digital reading tools in Indonesian schools. Recommends integrating digital media to improve English learning outcomes. Keywords: Let’s Read, Reading Comprehension, Digital Media, Junior High School, English Learning